Selected Drivers of Employee-Based Brand Equity and Perceived Corporate Reputation of Private Universities in Southern Region of Nigeria - Helen U. WARA; Anthonia A. ADENIJI; Ebeguki E. IGBINOBA; Samuel T. WARA (Communications of International Proceedings, 2021)
In a service-providing organisation like universities, the development and sustenance of a strong brand is usually seen as the principal function of the Marketing /Sales Department and Corporate Affairs Unit. This practice relegates the employees of other departments in the drive for competitive advantage and corporate reputation. Against this background, this study looked at selected drivers of Employee-Based Brand Equity and perceived corporate reputation in selected private universities in the Southern region of Nigeria. The study adopted the quantitative research method, using the questionnaire as the research instrument. Seven hundred (700) questionnaires (soft and hard copies) were administered to six private universities' academic and non-academic staff in the nation’s southern region. The randomly selected respondents returned only 594 copies of the questionnaires. The data collected were analysed using the Structural Equation Model (SEM), specifically the Partial Least Square. The results of the tested hypotheses revealed that information generation had a significant effect on financial performance at (β = 0.604, R2 = 0.365, t-statistics = 8.623 > 1.96, P-value = < 0.001). Also, knowledge dissemination had a significant effect on financial performance at (β = 0.647, R2 = 0.418, t-statistics =10.362 > 1.96, P-value = < 0.001). The findings revealed that the perceived corporate reputation of the universities by the employees affected their relationship with the institutions' external customers. It was recommended that the managers of private universities establish a feedback mechanism that enables employees to report their experiences on the field with universities external customers; utilise the feedback generated in the decision–making processes. It would spur a sense of belonging and importance in the employees towards the system.  It was also recommended that employees be educated on the institution's brand promise and institutionalised individual knowledge.
Keywords: Employee-Based Brand Equity; Corporate Reputation; Competitive Advantage; Private Universities